The Gnomes of Historia Lituana by Albertas Vijūkas Kojalavičius (Albertus Wiiuk Koialowicz) - Dilytė, Dalia (Senoji Lietuvos literatūra, 2017)
The narrative of Historia Lituana (The History of Lithuania) abounds in firm statements that are seemingly unquestionable and declare eternal truths. The term of gnomes was chosen to define these statements in this paper. Kojalavičius’s gnomes differ in their form. The most frequent is the version when a simple statement is expressed by a direct sentence. Some of them concisely express a generalized truth recognized by many. Another group consists of expanded gnomes: they appear when the author needs to give a broader explanation of his thought. Sometimes the gnomes are expressed as rhetorical questions, and others are like exclamations. Thematically, the gnomes of Lietuvos istorija can be divided into three groups. One group would consist of discerning general statements about the human nature, human interpersonal relations, and the common laws of life. A number of gnomes are related with the author’s attitude towards religious issues, and the largest group of the general statements in Lietuvos istorija focuses on various aspects of the internal life of the state and international politics. The gnomes dwell on different facets of these issues. The author keeps returning to the essence of citizens’ concord and obedience to power. Some gnomes define the elements of the rulers’ status, their demeanour, and their method of ruling. Others dwell on the relationships between states and people from different countries. As a rule, each gnome plays a number of roles in the text. One of the functions of a gnome would be the author’s commentary on an event narrated, which would assume the form of a generalization. Another function of a gnome would be the change of time. Like in all historical works, past tenses dominate Kojalavičius’s work. The present tense of the verbs prevalent in the gnomes introduces the sense of the present into the narrative told in past tenses. However, not only the grammatical form is significant here. Since the statements proclaiming eternal truths are timeless, the readers of all times accept them as the wisdom of their own time. Yet probably the most obvious and most frequent function of the gnomes in Historia Lituana, and the one that subjugates other functions, is that of the realization of the didactic purpose. In almost each gnome expressed by a direct sentence we find the affirmative words nam, enim, ita, quippe, nimirum, verum, quare, etc., which reveal the author’s aspiration to highlight and to prove the truth he had concentrated in the gnome, so that the readers believe and recognize it.